Correlation between productivity and centesimal composition of soybean cultivars - A. F. Fonseca; E. Neves; F. L. Dipple; T. C. Lima (Scientific Electronic Archives, 2020)
Soy soybean Glycine max (L) Merril is one of the main agricultural crops in Brazil. Thanks to the advances made by the breeding programs in recent years, the crop has achieved increasingly satisfactory results, especially with regard to the productivity of cultivated materials. One of the effects of the productive potential for the significant increase of the area planted throughout the national territory. Unfortunately one of the consequences of this genetic advance in the soybean materials produced was in relation to the chemical composition of the grains. In the last decades the centesimal composition of the soybean, especially protein, has suffered a significant discount. This is reflected in the overwhelming industries that find it increasingly difficult to produce bran with protein within the commercialized specifications, having to resort to a little profitable practice, the removal of the tegument from the grain to increase the protein in the bran produced. As the market operates through buying and selling by quantity and not grain quality, the sector begins to express concern due to uncertainties in the raw material. Thus, the present work has the objective of evaluating the existence of a correlation between productivity and the chemical composition of soybean cultivars. The cultivars were selected according to their productivity and divided into three classifications, high productivity, average productivity and low productivity, based on the work of the Rio Verde Foundation, totaling nine samples. The samples were evaluated through physicochemical analyzes to determine the percentage of coarse and fine moisture of the grains, percentage of acidity of the oil and percentage of protein and oil of the grains. All analyzes were done in triplicates and the results were submitted to analysis of variance (ANOVA), followed by a Tukey average comparison test at 5 %. The percentage of coarse moisture of cultivar 5 was the highest among all cultivars evaluated, with 10.43 %. In relation to the fine moisture, again the variety 5 obtained greater percentage among all the materials, with 9,17 %. Regarding the percentage of acidity, cultivars 4, 2 and 3 obtained the highest results with values between 0.51 % and 0.46 %. The percentage of oil of cultivar 3 obtained the highest percentage, with 21.96 %. Regarding the percentage of protein, cultivar 5 presented the highest percentage of protein among all, with 35.78 %. All results are presented within acceptable industry standards. Through the analyzes can see a tendency to low negative correlation between productivity and protein content. There is also a low negative correlation between oil and protein dyes. Positive highlight for the performance of cultivar 5 by good correlation between productivity and protein contents.